Perancangan Panti Rehabilitasi Ketergantungan Narkotika dan Psikotropika di Gorontalo dengan Konsep Arsitektur Perilaku - Gufran Al-Gifary Y. Duhengo; M Fauzhan Algiffari; Frans Mitran Ajami (Politeknik Kebangsaan, 2026)
The abuse of narcotics and psychotropic substances in Gorontalo Province has shown a significant upward trend, with Gorontalo ranking 8th nationally in drug use in 2016. Despite fluctuations in the number of medical rehabilitation patients between 2016 and 2023, the existing inpatient facilities at Tombulilato Regional General Hospital are no longer sufficient to handle the complexity of cases across various age groups and backgrounds. This research aims to analyze spatial patterns and facilities while formulating the application of the Behavioral Architecture approach in designing a Narcotics and Psychotropic Rehabilitation Center in Gorontalo City. The research method employed is descriptive qualitative, with data collection techniques including field observations in Molosipat W, literature reviews, and comparative studies. The Behavioral Architecture approach is applied as a design solution to create a built environment that is responsive to the psychological conditions and behaviors of the users. The design focus encompasses recreative, educative, therapeutic, and conservation aspects to support holistic physical and mental recovery. The results of this study produce a regional-scale rehabilitation center design that integrates medical and social rehabilitation units with creativity development facilities. Through strategic spatial configuration, color selection, and a strong connection with nature, this design is expected to restore self-confidence and social functioning, enabling individuals to return to society independently.